Организация ледокольной проводки транспортных судов - Abramov, Aleksei Vasilievich; Zagorodnikov, Mikhail (Administrativa Consulting, 2025)
Various making tactics of transportation of freights on Northern Sea Route are given in article. Offers on distribution of innovative ice breakers on routes Northern Sea Route are given.